The Essence of Building National Integration Values Through Civility Education Courses of PPKN - Priazki Hajri (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2023)
ABSTRACTThe purpose of this study is to see how the essence of building national integration values through civic education among students is based on the urgency of national integration values which need to always be implemented in everyday life with the aim of avoiding division and disintegration. One of the achievements in the citizenship education course is transmitting the values of tolerance, insight into diversity, and instilling the value of nationalism with the ultimate goal of creating complete national integration. The method used in this study is a qualitative method with a descriptive approach, the data collected is class observation data and literature that supports the concept of national integration. Answering the formulation in this study, the research results obtained were that the researcher found three main essences in building national integration through civics courses in students, first, namely as a means of building unity, where campuses consisting of students who have different backgrounds can unite in one goal of education, second, through citizenship education students can increase their nationalism and understanding of nationality, and third, students are trained to be able to increase tolerance and solidarity among students and teach them that differences do not make us different but it is division that will make us different.Keywords: National integration, civics education, PPKn students.